An Imported Case of Echinococcosis in a Pregnant Lady with Unusual Presentation. (17th January 2013) - Al-Ani, Ahmed; Elzouki, Abdul-Naser; Mazhar, Rashid
Abstract : A 31-year-old Syrian pregnant (25-week duration) patient who was managed as a case of bronchial asthma for one year because of chronic cough and progressive breathlessness presented to the Accident and Emergency Department at Hamad General Hospital, Doha, with cough and shortness of breath. On the day of admission, she coughed large amount of yellowish watery material which was salty and sour in taste. She was found by radiological investigations to have multiple giant hydatid cysts (three in the lungs and one in the liver), with ruptured cyst in the left lung. We report here an unusual case of giant multiple pulmonary hydatidosis localized in the lungs and masquerading as bronchial asthma in a pregnant lady. The case represents an uncommon situation of a common disease of rupture of hydatid cyst of the lung in a pregnant lady in her 3rd trimester.